A satellite study of the Orissa cyclonic storm of October 1967 - KULSHRESTHA, S. M. (MAUSAM, 1971)
A cyclonic storm hit Orissa coast on.9 October 1967. This cyclonic storm, of mall extent, appeared to be quite intense and had many notable features, which are discussed III this paper with the help of the cloud cover photographs obtained from the ESSA.3 satellite.